PREVALENCE OF CO INFECTION IN PEOPLE LIVING WITH HIV ATTENDING STI CLINIC AT TERTIARY CARE HOSPITAL, HYDERABAD TELANGANA - Dr. Arun Kumar Joshi; Dr. M.L. Kavitha Latha; Dr. A. Nanditha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
INTRODUCTION: HIV remains a major global public health issue, having claimed an estimated 42.3 million lives till date. Transmission is ongoing in all countries globally According to NACO Sexually transmitted infections (STI) rank among the top five conditions for which sexually active adults seek health care in the developing countries. As per the community based STI/RTI prevalence study over 6% of the adult population in India suffers from one or the other STI/RTI episode annually. Presence of a STI/RTI in the sexual partner increases the risk of acquisition of HIV from an infected partner by 8-10-fold Effective control of STI/RTI is a strong and most cost-effective strategy for reducing/preventing transmission of HIV. METHODS: Patient were screened and detailed history was taken. Appropriate samples were collected based on patient complaints such as serum for screening for HIV, HBsAg, HCV, HSV (rapid and ELISA) Syphilis (TPHA &VDRL) , discharge from abscess in suspected cases of herpes simplex virus (HSV) or varicella-zoster virus (VZV). RESULTS: During the study period of 6 months from January 2024 to June 2024 a total of 610 patients living with HIV visited the STI clinic with symptoms of STI. Comprehensive analysis and testing revealed Disease of bacterial aetiology syphilis in 116(19.01%); Diseases of viral aetiology: HBsAg positive in 18(2.9%), HCV positive in 2(0.32%), Genital ulcer disease herpetic (HSV 2) in 12 (1.9%) Genital molluscum (molluscum contagiosum) in 10 (1.63%); disease of parasitic aetiology Genital Scabies in 7 (1.14%) and disease of fungal aetiology: Taenia in 9 (1.47%). CONCLUSIONS: Our study shows, increasing incidence of new STI coinfections in PLVH, thereby decreasing their quality of life, noncompliance to treatment and increasing morbidity. Periodic counselling with assertion of safe sex and regular screening for STIs should be norm for early detection and starting appropriate treatment in these patients to improve their quality of life.